GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG KEPUTIHAN PADA KELAS X DI SMK NEGERI 3 PURWOKERTO PERIODE JULI-AGUSTUS 2009 - Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2009)
Whitish is a very frequent symptom experienced by most women. Based on a survey of teenage girls in class X in SMK Negeri 3 Purwokerto found that 7 out of 10 young women experience vaginal discharge and say not knowing about the definition, causes and treatment in case of vaginal discharge. Objective: To determine the knowledge level overview of the white girls at SMK Negeri 3 Purwokerto, Banyumas Regency period July August, 2009. Methods: The study was descriptive quantitative research with cross sectional approach. The study population were teenage girls in class X in SMK Negeri 3 Purwokerto as many as 200 people. These samples included 50 people by using simple random sampling technique. The instrument used was a questionnaire. Results: Overview of the young women knowledge about vaginal discharge in class X in SMK Negeri 3 Purwokerto period July-August 2009 is known mostly have poor knowledge about vaginal discharge (48.0%), an overview of knowledge by understanding whitish young women mostly have poor knowledge (40.0%), based on the cause of vaginal discharge mostly have poor knowledge (42.0%), based on the prevention and treatment of vaginal discharge mostly have poor knowledge (40.0%). Conclusion: Overview of the young women knowledge about vaginal discharge in class X in SMK Negeri 3 Purwokerto period JulyAugust 2009 is known mostly have poor knowledge and a fraction having good knowledge. Keywords: Knowledge, Young Women, Whitish